Maintenance therapy of childhood acute lymphoblastic leukemia revisited—Should drug doses be adjusted by white blood cell, neutrophil, or lymphocyte counts?. Issue 12 (22nd July 2016) - Schmiegelow, Kjeld; Nersting, Jacob; Nielsen, Stine Nygaard; Heyman, Mats; Wesenberg, Finn; Kristinsson, Jon; Vettenranta, Kim; Schrøeder, Henrik; Weinshilboum, Richard; Jensen, Katrine Lykke; Grell, Kathrine; Rosthoej, Susanne; et al.
Abstract: Background: 6‐Mercaptopurine (6MP) and methotrexate (MTX) based maintenance therapy is a critical phase of childhood acute lymphoblastic leukemia treatment. Wide interindividual variations in drug disposition warrant frequent doses adjustments, but there is a lack of international consensus on dose adjustment guidelines. Procedure: To identify relapse predictors, we collected 28, 255 data sets on drug doses and blood counts (median: 47/patient) and analyzed erythrocyte (Ery) levels of cytotoxic 6MP/MTX metabolites in 9, 182 blood samples (median: 14 samples/patient) from 532 children on MTX/6MP maintenance therapy targeted to a white blood cell count (WBC) of 1.5–3.5 × 10 9 /l. Results: After a median follow‐up of 13.8 years for patients in remission, stepwise Cox regression analysis did not find age, average doses of 6MP and MTX, hemoglobin, absolute lymphocyte counts, thrombocyte counts, or Ery levels of 6‐thioguanine nucleotides or MTX (including its polyglutamates) to be significant relapse predictors. The parameters significantly associated with risk of relapse (N = 83) were male sex (hazard ratio [HR] 2.0 [1.3–3.1], P = 0.003), WBC at diagnosis (HR = 1.04 per 10 × 10 9 /l rise [1.00–1.09], P = 0.048), the absolute neutrophil count (ANC; HR = 1.7 per 10 9 /l rise [1.3–2.4], P = 0.0007), and Ery thiopurine methyltransferase activity (HR = 2.7 per IU/ml rise [1.1–6.7], P = 0.03). WBC was significantly related to ANC (Spearman correlation coefficient, rs = 0.77; P < 0.001), and only a borderline significant risk factor for relapse (HR = 1.28 [95% CI: 1.00–1.64], P = 0.046) when ANC was excluded from the Cox model. Conclusions: This study indicates that a low neutrophil count is likely to be the best hematological target for dose adjustments of maintenance therapy.